2017
DOI: 10.1002/pssr.201700256
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transport in a Quantum Wire Driven by Spin–Orbit Interaction

Abstract: We consider a gated one-dimensional (1D) quantum wire disturbed in a contactless manner by an alternating electric field produced by a tip of a scanning probe microscope. In this schematic 1D electrons are driven not by a pulling electric field but rather by a non-stationary spin-orbit interaction (SOI) created by the tip. We show that a charge current appears in the wire in the presence of the Rashba SOI produced by the gate net charge and image charges of 1D electrons induced on the gate (iSOI). The iSOI con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…e form of the PSOI Hamiltonian in a speci c low-dimensional structure is determined by the con guration of the Coulomb elds therein. In a 1D quantum wire the only source of the PSOI is the Coulomb eld of e-e interaction directed normally to the wire, which appears if the system is not symmetric in the radial direction [4][5][6][7]. Such asymmetry can be created, for example, by a proximate metallic gate.…”
Section: Electrostatics and Psoi In Low-dimensional Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…e form of the PSOI Hamiltonian in a speci c low-dimensional structure is determined by the con guration of the Coulomb elds therein. In a 1D quantum wire the only source of the PSOI is the Coulomb eld of e-e interaction directed normally to the wire, which appears if the system is not symmetric in the radial direction [4][5][6][7]. Such asymmetry can be created, for example, by a proximate metallic gate.…”
Section: Electrostatics and Psoi In Low-dimensional Systemsmentioning
confidence: 99%
“…It is clear that the behavior of the many-electron system depends on both e ects, the relative role of which is yet to be determined. In this section we focus on the PSOI-driven instability of the strongly correlated 1D electron liquids and on the PSOI signatures in electron transport in quantum wires [5,6]. e instability of the many-electron system is due to a qualitatively new property of PSOI, as compared to the single-electron Rashba SOI.…”
Section: Psoi In a Many-electron Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that in low-dimensional systems the SOI produced by the Coulomb interaction of electrons with the image charges induced on a nearby metallic gate leads to nontrivial effects in materials with large Rashba SOI constants [4][5][6]. The main effect is that because of this interaction, the electronelectron (e-e) interaction Hamiltonian acquires a spin-dependent component that is attractive for a particular spin orientation locked to momentum.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [3][4][5] these effects have been studied for the spin-orbit interaction caused by the potential of image charges (iSOI) that electrons induce on a metallic gate placed nearby. The main result is the fact that the spin-dependent component of the e-e interaction Hamiltonian produced by the iSOI is attractive for a particular spin orientation locked to momentum.…”
Section: Introductionmentioning
confidence: 99%